A potential study for developing Sebuyau, Simunjan as an ecotourism destination / Rozina Rafaiee - Rafaiee, Rozina (2009)
Tourism represent most economic development to Sarawak where Sarawak the place that have unique cultures with 27 different ethnics that might attract the tourists all over the world. Although the potential of ecotourism at rural area requires careful planning and so much research that must be study before the place might be develop as an ecotourism destination. Forest at rural areas that will be developed have its historical value that very valuable to the local people and which is considered to be well preserve by them. All ofthe natural resources at rural area are protected by government and any activities such as lodging and illegal hunting that might harm the nature of flora and fauna are illegal and it is the best way for government to reserve as National Park.